DNase enhances photodynamic therapy against fluconazole-resistant Candida albicans biofilms - Abreu-Pereira, César Augusto [UNESP] (2022)
Objective: This study evaluated the effectiveness of DNase I combined with antimicrobial photodynamic therapy, mediated by Photodithazine® and light-emitting diode light, against biofilms formed by a fluconazole-resistant Candida albicans strain (ATCC 96901) and two clinical isolates (R14 and R70). Materials and Methods: Biofilms were grown for 48 h and exposed to DNase for 5 min, followed by application of a photosensitizer (P) and light (L), either singly or combined (P+L+, P−L+, P+L−, P−L−, P−L−DNase, P+L+DNase, P+L−DNase, and P−L+DNase; n = 12). Biofilm analysis included quantification of extracellular matrix components (water-soluble and insoluble polysaccharides, proteins and extracellular DNA), and biomass (total and insoluble), as well as the enumeration of colony-forming units. The data were analyzed using three-way analysis of variance with Bonferroni's post hoc test. Results: The DNase treatment combined with aPDT showed a reduction of 1.92, 1.65, and 1.29 log10 of cell viability compared with untreated controls for ATCC 96901, R14, and R70 strains, respectively. It also reduced extracellular matrix contents of water-soluble polysaccharides (36.3%) and extracellular DNA (72.3%), as well as insoluble biomass content (43.3%). Conclusion: The three strains showed similar behavior when treated with DNase, and the extracellular matrix components were affected, improving the effectiveness of antimicrobial photodynamic therapy.